Effectiveness Of Interaction Analysis Feedback On The Verbal Behaviour Of Primary School Mathematics Teachers - See, Kin Hai*; Lim , Siew Bee (Penerbit Universiti Sains Malaysia, 2006)
This study attempted to investigate the relative effectiveness of interaction analysis feedback on the verbal behaviour of teachers teaching mathematics in Primary 5 classes of four randomly selected primary schools in Brunei-Muara district. It also attempted to investigate the effects of the feedback system on pupils' attitude towards mathematics and their academic achievement in mathematics. The sample used for the study consisted of eight primary school teachers teaching mathematics subject. These eight teachers were preselected and were divided into feedback (experimental) and nonfeedback (control) groups. One teacher from each of the four schools was selected as the experimental group and the other teacher from the same school was picked as the control group. One hundred and fifty two pupils of average ability from four urban schools were involved. To examine the extent to which the feedback system was effective, a modified Flanders Interaction Analysis Categories System (FIACS) was used to record classroom communications and the results provided as a feedback to the experimental group. Results showed that the feedback groups accepted students feelings more, praised students more, used students' ideas and initiated more student talk in the classroom. Effects of the feedback were encouraging with higher student academic achievement and more favourable attitudes after teachers were given feedback.